2014
DOI: 10.1007/s00360-014-0823-2
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpic consequences of reduced chloride binding in Andean frog (Telmatobius peruvianus) hemoglobin

Abstract: Based on the exothermic nature of heme oxygenation, the O2 affinity of hemoglobin (Hb) decreases with increasing temperature, which may be physiologically advantageous in augmenting O2 unloading from blood in warm tissues with elevated metabolic rates. This negative oxygenation enthalpy (∆H (O)) may, however, become maladaptive, as in cold-tolerant ungulates where it may hamper O2 unloading in cold extremities and commonly is mitigated by an 'additional' chloride-binding site that decreases the temperature eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…⌬H O2 and ⌬H H2O are rather invariable across species; hence, the temperature sensitivity of O 2 binding is largely dependent on ⌬H cc and oxygenation-linked endothermic release of allosteric effectors (61). Therefore, a relationship exists between the number of binding sites for allosteric effectors and the temperature sensitivity of O 2 binding (8,60,62), where Hbs with multiple binding sites have a low temperature sensitivity, and vice versa. It has been suggested that the higher number of effector binding sites and, thus, low temperature sensitivity of O 2 binding, is beneficial in regionally heterothermic animals, where O 2 unloading can for example, be safeguarded to the extremities of Arctic mammals (7,8,15), and where O 2 delivery can be regulated to warm brains and swimming muscles of tuna, shark, and billfishes (9,31,62).…”
Section: Gtpmentioning
confidence: 99%
“…⌬H O2 and ⌬H H2O are rather invariable across species; hence, the temperature sensitivity of O 2 binding is largely dependent on ⌬H cc and oxygenation-linked endothermic release of allosteric effectors (61). Therefore, a relationship exists between the number of binding sites for allosteric effectors and the temperature sensitivity of O 2 binding (8,60,62), where Hbs with multiple binding sites have a low temperature sensitivity, and vice versa. It has been suggested that the higher number of effector binding sites and, thus, low temperature sensitivity of O 2 binding, is beneficial in regionally heterothermic animals, where O 2 unloading can for example, be safeguarded to the extremities of Arctic mammals (7,8,15), and where O 2 delivery can be regulated to warm brains and swimming muscles of tuna, shark, and billfishes (9,31,62).…”
Section: Gtpmentioning
confidence: 99%
“…at Lys8β, Lys76β, His77β), given the evidence that yet other amino groups within the central cavity of bovine Hb (including Lys103β that is at a homologous position to Arg104β of human Hb) may be considered functional Cl − -binding sites (Ueno and Manning, 1992). Regardless, the negative correlation between the overall number of Cl − -binding sites and the temperature sensitivity of Hb-O 2 affinity remains valid, and is supported -and extended to lower vertebrates -by the distinctly higher temperature dependence of O 2 affinity encountered in Andean frog Telmatobius peruvianus Hb that lacks the α-chain Cl − -binding site, compared to that found in lowland toad Xenopus laevis Hb that has retained this Cl − -binding site (Weber, 2014).…”
Section: Oxygenation Enthalpiesmentioning
confidence: 77%
“…2017; Muñoz‐Saravia 2018), as well as to enduring low oxygen levels and pronounced temperature fluctuations (Hutchison et al . 1976; Weber 2014; Muñoz‐Saravia et al . 2018).…”
Section: Figmentioning
confidence: 99%
“…The genus name Telmatobius, as their common name (Water frogs), alludes to their mostly aquatic habits in a variety of environments, including mountain streams of temperate humid realms such as cloud forests, as well as streams, ponds, peat bogs, thermal springs, and lakes of the colder and drier highlands of the Altiplano and Puna (Vellard 1951;De la Riva 2005;Barrionuevo 2017). The aquatic highland species adapted to the harsh conditions of highland environments (Vellard 1951;Sáez et al 2022), such as the endangered Titicaca Water Frog (Telmatobius culeus; IUCN SSC Amphibian Specialist Group 2020), show morphological, physiological, and ecological peculiarities related to feeding and communicating underwater Brunetti et al 2017;Muñoz-Saravia 2018), as well as to enduring low oxygen levels and pronounced temperature fluctuations (Hutchison et al 1976;Weber 2014;Muñoz-Saravia et al 2018).…”
Section: Introductionmentioning
confidence: 99%